Dermatology clinical case - Marques, Telma Luís; Clemêncio, Tatiana; Santos, Lea; Loureiro, Manuela (BIRTH AND GROWTH MEDICAL JOURNAL, 2022)
The case of a teenager with guttate psoriasis secondary to trauma and upper airway infection is reported. Guttate psoriasis is the second most common psoriasis variant in pediatric age. Infection and trauma (leading to Koebner phenomenon) seem to be major triggers of the condition. The diagnosis is clinical. Most cases with no previous history of psoriasis spontaneously remit. Topical corticosteroids and vitamin D analogs, as well as phototherapy, are the first-line treatments.